KAKAWIN ATLAS BH?MI SEBUAH KAJIAN RESEPSI SASTRA - Putu Arcana, Ida Bagus (Humanis; Volume 11. No 1. April 2015)
Research on the Atlas Kakawin Bhumi is motivated by the major reasons, namely because kakawin is unique when compared to other kakawin. Kakawin-kakawin previously mostly use a theme that is both epic while Kakawin Atlas Bhumi using themes related to worldatlas. Therefore kakawin writer to have been investigated. This study aims to examine the structure of the Atlas Kakawin Bhumi, both formal structure and narrative structure. Besides, this study aims to assess the shape of the reception Kakawin Atlas Bhumi. The method used in the data collection method is listening. At the stage of data analysis, the data obtained were processed using descriptive analytical methods and the data were analyzed according to the principles and practices of literary reception theory as the main runway. Approach reception is actually a continuation of structuralism approach. Therefore, the theory of the structure is not specifically addressed in this study. The results obtained in this study is the unfolding structure that builds the Atlas Bhumi Kakawin both formal structure and narrative structure. Formal structure Kakawin Bhumi Atlas includes teacher-laghu, wr?tta, Matra, Gana, canda, carik, pada, and pupuh. Atlas Bhumi Kakawin narrative structure includes manggala, corpus and epilogue, the narrative units Kakawin Atlas Bhumi and devices of narrative continuity Kakawin Atlas unit Bhumi. And the disclosure form Kakawin reception Atlas Bhumi include:the essence of the teachings of Goddess Saraswati in Kakawin Atlas Bhumi, cosmology in Kakawin Atlas Bhumi, and boundaries in Kakawin Atlas Bhumi
Keywords: kakawin, structure, and receptions